MENEGASKAN KARAKTER PENDIDIKAN NONFORMAL - Dinno Mulyono (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2012)
Nonformal education has a great role in modern education system. Since its introducing by Ahmed and Coombs in 1964, nonformal education has been seen as panachea for all education problems, include the further education for adult people or disadvantage people that can’t access the formal education. But, in other hands, nonformal education had been seen as the shadows of formal education. It’s happens when nonformal education doesn’t contribute the people with a real compensation for their lives.